If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(-9y + 8) + -4y = 2(y + -7) + -6 Reorder the terms: -2(8 + -9y) + -4y = 2(y + -7) + -6 (8 * -2 + -9y * -2) + -4y = 2(y + -7) + -6 (-16 + 18y) + -4y = 2(y + -7) + -6 Combine like terms: 18y + -4y = 14y -16 + 14y = 2(y + -7) + -6 Reorder the terms: -16 + 14y = 2(-7 + y) + -6 -16 + 14y = (-7 * 2 + y * 2) + -6 -16 + 14y = (-14 + 2y) + -6 Reorder the terms: -16 + 14y = -14 + -6 + 2y Combine like terms: -14 + -6 = -20 -16 + 14y = -20 + 2y Solving -16 + 14y = -20 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. -16 + 14y + -2y = -20 + 2y + -2y Combine like terms: 14y + -2y = 12y -16 + 12y = -20 + 2y + -2y Combine like terms: 2y + -2y = 0 -16 + 12y = -20 + 0 -16 + 12y = -20 Add '16' to each side of the equation. -16 + 16 + 12y = -20 + 16 Combine like terms: -16 + 16 = 0 0 + 12y = -20 + 16 12y = -20 + 16 Combine like terms: -20 + 16 = -4 12y = -4 Divide each side by '12'. y = -0.3333333333 Simplifying y = -0.3333333333
| x^2+308=540 | | Y=7+1.50*4 | | -16t^2+60t+0=h | | 1x+15=26 | | 3[4-2(3-8)]= | | 3-19w=-6w+41 | | x^2-232=0 | | Y=7+1.50*x | | 3=59+5x | | 2377960+26x=2396940 | | 35=3x+2 | | 10=7+1.50x | | -9+18x^2-2= | | 3+5[4-(6-2)]= | | 2396940+26x=2396940 | | 7=7+1.50x | | 6x^2+9x=362 | | 5(-2)+8-2(-2)+9(-2)=-16 | | 5y+3=-6y+6 | | 5x-30=6x+30 | | Y=7+1.50x | | 3p-7=10p | | 5+5-5=x | | 3.4x-4=2.4x | | 6+[2-(5-8)]= | | x+x+1+x+2=111 | | 60(6x)=40+10x | | t*30=210 | | 18x^2-48x+16=0 | | t*30=180 | | 5(-2)+8-2(-2)-9(-2)=-16 | | 5+5-5/5*5 |